2020
DOI: 10.3389/fpls.2019.01749
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Vegetation Indices to Track Senescence Dynamics in Diverse Wheat Germplasm

Abstract: The ability of a genotype to stay green affects the primary target traits grain yield (GY) and grain protein concentration (GPC) in wheat. High throughput methods to assess senescence dynamics in large field trials will allow for (i) indirect selection in early breeding generations, when yield cannot yet be accurately determined and (ii) mapping of the genomic regions controlling the trait. The aim of this study was to develop a robust method to assess senescence based on hyperspectral canopy reflectance. Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 69 publications
(99 reference statements)
4
90
0
1
Order By: Relevance
“…It seems highly questionable whether the PSRI is particularly sensitive to the Car/Chl ratio in diverse germplasm at the canopy level. Variation in the PSRI seems to arise primarily from differences in canopy structure among genotypes and from canopy structural changes over time (Anderegg et al, 2019, submitted ). The modified chlorophyll absorption ratio index (MCARI2; Haboudane et al, 2004), sensitive to green leaf area index, also showed strongly contrasting dynamic patterns ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It seems highly questionable whether the PSRI is particularly sensitive to the Car/Chl ratio in diverse germplasm at the canopy level. Variation in the PSRI seems to arise primarily from differences in canopy structure among genotypes and from canopy structural changes over time (Anderegg et al, 2019, submitted ). The modified chlorophyll absorption ratio index (MCARI2; Haboudane et al, 2004), sensitive to green leaf area index, also showed strongly contrasting dynamic patterns ( Figure 2B ).…”
Section: Discussionmentioning
confidence: 99%
“…; soil type: eutric cambisol), in the wheat growing season of 2017–2018. A subset of 18 bread wheat ( Triticum aestivum ) genotypes was selected from the genom-analyse in biologischen system pflanze (GABI) wheat panel (Kollers et al, 2013; complemented with Swiss cultivars) for contrasting levels of resistance to STB and for contrasting stay-green properties based on previous experiments at the same location (Anderegg et al, 2019, submitted to this issue ; Karisto et al, 2018). The set comprised morphologically diverse genotypes (e.g., awned and unawned), and there were obvious differences in canopy structural parameters (e.g., flag leaf angle) among the selected genotypes ( Supplementary Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations